Writing English Thesis in The Habitus New Normal Post Covid-19: Obstacles and Challenges from The Students’ Perspective - Ayuliamita Abadi; Rahmadani Putri; Diah Dwi Santri; Aryawira Pratama; Mayang Sastra Saumardi; Khotimah Mahmudah; Wahyuni Fitria; Edi Rozal (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2023)
The majority of learning and teaching activities during the COVID-19 era were distributed to remote learners. The ineffectiveness of face-to-face instruction was subsequently put aside as students felt comfortable learning online. Policymakers in the education system had to adjust to a new normal or habit once the COVID-19 cases started to decline. The aim of this research is to identify the challenges faced by final year students in completing thesis during the Post-Covid-19 New Normal Habitus period and to find out how final year students can complete their thesis guidance during the Post-Covid-19 New Normal Habitus period. There were 15 English students joining the interview and the research was conducted within the State Islamic campus in Jambi City. Coding system was implemented to get credible data. The result shows that Completing studies in the New Normal Era has several obstacles. One of the most significant problems is the communication problem between students and supervisors which involves internal and external factors. Internal factors focus on difficulties caused by students' lack of understanding of thesis components, references and citation styles. Meanwhile, external factors focus on students' difficulties in the thesis writing process which depends on the direction of the supervisor, where some lecturers still provide online thesis guidance, where students agree that online counseling is not effective.